2016
DOI: 10.2147/ndt.s110571
|View full text |Cite
|
Sign up to set email alerts
|

Brief behavioral treatment for patients with treatment-resistant insomnia

Abstract: ObjectiveTo evaluate the efficacy of brief behavioral treatment for insomnia (BBTI) in treating patients with treatment-resistant insomnia.MethodsSeventy-nine adults with treatment-resistant insomnia were randomly assigned to receive either individualized BBTI (delivered in two in-person sessions and two telephone “booster” sessions, n=40) or sleep hygiene education (n=39). The primary outcome was subjective (sleep diary) measures of self-report symptoms and questionnaire measures of Pittsburgh sleep quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
4
21
0
Order By: Relevance
“…SOL decreased from 33 min to 21 min, and post-intervention average SOL was reported to be within normal limits [ 68 ]. This was consistent with previous studies that showed significant improvement in sleep indices following BBTi in various target groups such as the elderly and adult insomnia patients [ 23 , 24 , 28 ]. There were also improvements for insomnia severity and daytime sleepiness scores, suggesting that brief intervention is helpful in alleviating sleep disturbance in this population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…SOL decreased from 33 min to 21 min, and post-intervention average SOL was reported to be within normal limits [ 68 ]. This was consistent with previous studies that showed significant improvement in sleep indices following BBTi in various target groups such as the elderly and adult insomnia patients [ 23 , 24 , 28 ]. There were also improvements for insomnia severity and daytime sleepiness scores, suggesting that brief intervention is helpful in alleviating sleep disturbance in this population.…”
Section: Discussionsupporting
confidence: 93%
“…Brief behavior therapy for insomnia (BBTi) is a short-term sleep intervention that facilitates high patient compliance because of shorter delivery time compared to traditional cognitive-behavioral therapy for insomnia (CBTi) [ 23 , 24 ]. BBTi was developed to address common barriers, such as the duration of treatment sessions and the number of specialty-trained clinicians available that is encountered in the provision of evidence-based CBTi [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RACGP benzodiazepine guideline supports the use of BBTi, which can be delivered by general practitioners (GPs) and practice nurses with minimal training and without the need for costly overnight sleep studies. 7,15 Despite the shorter duration, BBTi is effective in a diverse group of patients with insomnia, including in older adults, 13 comorbid depression, 16 hypnotic-resistant insomnia 17 and individuals living with human immonodeficiency virus. 18 Furthermore, BBTi assists patients in withdrawing from sedative-hypnotic medications, by improving sleep and reducing withdrawal/ rebound insomnia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, BBTi assists patients in withdrawing from sedative-hypnotic medications, by improving sleep and reducing withdrawal/ rebound insomnia symptoms. 17 A step-by-step model for a brief behavioural treatment for insomnia in Australian general practice Importantly, several previous studies have shown the feasibility and efficacy of BBTi and other brief CBTi interventions in general practice settings, 19,20 and when administered by practice nurses. 14,20 Insomnia and depression/anxiety disorders commonly co-occur.…”
Section: Discussionmentioning
confidence: 99%